Особливостi приповерхневого шару при мономолекулярнiй iзотропнiй адсорбцiї: моделювання в рамках нерiвноважної молекулярної динамiки - Manoilov, E. G.; Kravchenko, S. A.; Snopok, B. A. (Publishing house "Academperiodika", 2018)
Processes running in the gas phase near a solid surface have been analyzed in the framework of nonequilibrium dynamics and by simulating the irreversible monomolecular isotropic adsorption. Their influence on the adsorption kinetics is analyzed. A complicated spatial organization of particles in the near-surface layer, where the particle concentration and energy vary in time, is revealed,. It is found that the local particle concentration can either decrease (down to about 60% of the initial value) or increase with the distance from the surface, depending on the system concerned. The obtained results can be used to analyze and to predict processes running in the near-surface layer of elements for the sensor and electronic engineering, gas dynamics, and other areas, where the ballistic character and the kinematics of motion dominate and govern the functional properties of the system.